Nutritional compositions and antioxidant activities of non-polar and polar extracts of germinated brown rice - Lim, See Meng; Goh, Yong Meng; Loh, Su Peng (Universiti Putra Malaysia Press, 2016)
The objective of this study was to investigate the nutritional compositions and antioxidant activities (AA) of non-polar and polar extracts of germinated brown rice (GBR). Nutritional compositions such as moisture, ash, carbohydrate, fat, protein and fibre were determined. Energy and minerals content were determined by using bomb calorimetry and Atomic Absorption Spectroscopy (AAS), respectively. Total phenolic content (TPC) and total flavonoid content (TFC) of the extracts were determined by Folin-Ciocalteu method and aluminium chloride colorimetric method. The AA was determined using 2,2-diphenyl-1-picrylhydrazyl (DPPH) and [2,2′-Azinobis(3-ethylbenzothiazoline-6-sulfonic acid)] diammonium salt (ABTS) radical scavenging capacity assay, ferric reducing antioxidant potential (FRAP) assay, and β-carotene bleaching assay. Total energy content of GBR sample was 390.95±11.31 kcal/100g and carbohydrate (54.30±1.04 g/100 g) was the most abundant nutrient. The predominant minerals in the GBR sample were sodium, potassium and magnesium. The polar extract showed significantly higher (p<0.05) level in TPC, TFC and AA than non-polar extract except in β-carotene bleaching assay. Positive and strong correlations (r>0.90, p<0.001) existed between antioxidants (TPC and TFC) and AA. Therefore, polar extract was better than non-polar extract. The nutritional composition of GBR also provided an update for food composition database.